2013
DOI: 10.1002/lpor.201300118
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and high-efficiency conversion from guided waves to spoof surface plasmon polaritons

Abstract: The conversion from spatial propagating waves to surface plasmon polaritons (SPPs) has been well studied, and shown to be very efficient by using gradient‐index metasurfaces. However, feeding energies into and extracting signals from functional plasmonic devices or circuits through transmission lines require the efficient conversion between SPPs and guided waves, which has not been reported, to the best of our knowledge. In this paper, a smooth bridge between the conventional coplanar waveguide (CPW) with 50 Ω… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
348
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 598 publications
(354 citation statements)
references
References 25 publications
4
348
0
2
Order By: Relevance
“…J. Pendry et al reported that structured metal surface can support and propagate SSPPs [7]. In order to produce high transmission efficiency between single wire and coplanar waveguide (CPW), many efforts have been made [11][12][13][14]. As we know, SSPPs have good characteristics of high field confinement, planar configuration and deep-subwavelength, so we can take the advantage of the SSPPs to fabrication circulator.…”
Section: Introductionmentioning
confidence: 99%
“…J. Pendry et al reported that structured metal surface can support and propagate SSPPs [7]. In order to produce high transmission efficiency between single wire and coplanar waveguide (CPW), many efforts have been made [11][12][13][14]. As we know, SSPPs have good characteristics of high field confinement, planar configuration and deep-subwavelength, so we can take the advantage of the SSPPs to fabrication circulator.…”
Section: Introductionmentioning
confidence: 99%
“…On a broad scale, electromagnetic band gap [1] (EBG), high impedance surface (HIS) [2], frequency selective surface (FSS) [3], [4], polarization rotation surface (PRS) [5], [6], artificial magnetic conductor (AMC) [7][8][9][10], perfect absorbing material (PMA) [11][12][13][14] and spoof surface plasmon polaritons (SSPP) [15], [16] could be classified into the category of MS, among which AMC (easy processing and flexible in manipulating the reflection phase) and PMA (extremely low profile) draw increasingly interest of the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…from propagation wave to SSPPs and utilizing these ultra-thin plasmonic metamaterial to design plasmonic devices. [15][16][17][18][19][20] However, the studies on improvement of characteristic and enhancement of confinement capacity of SSPPs, which are highly demanded in design of various miniaturized devices and circuitries, have not been paid much attention on. Compare to traditional structures with rectangular grooves or trapezoidal grooves, this proposed structure shows strong confinement of SPPs which means it has less transmission loss of SSPPs and more propagation length.…”
Section: Introductionmentioning
confidence: 99%